A distinctive case of gastrosplenic fistula: comprehending melioidosis - T. J., Clement Prakash; Abraham, John; Akhoury, Ambikha; Sophia, S.; Jacob, Anieta Merin (International Surgery Journal, 2024)
This case report delves into an exceedingly rare case of gastrosplenic fistula and concurrent upper GI bleeding in the setting of melioidosis. Although upper GI bleeding is often encountered in the clinical setting, the co-existence of a gastrosplenic fistula adds an unprecedented amount of complexity. Melioidosis is an infectious disease endemic to certain geographic regions of the world, namely that of Southeast Asia and Northern Australia. Burkholderia pseudomallei, the culprit organism, is associated with bioterrorism on account of which it has gained notoriety in recent years. This case underscores the array of diagnostic challenges that were combated and the prompt surgical intervention in the form of a splenectomy and partial gastrectomy that culminated in a favorable outcome. Coordination in a temporal fashion and multidisciplinary collaboration between surgeons and physicians was imperative to success. This report emphasizes the significance of recognizing and addressing the atypical manifestations of the disease as it challenges the conventional understanding of melioidosis and offers significant insights into the realm of infectious disease, at large.